Crisis and turnaround in German medium-sized enterprises : an integrated empirical study - Wittig, Thomas, 1960- (Springer Fachmedien Wiesbaden, 2017)
Thomas Wittig aims at gaining additional insights into the crisis and turnaround process of SMEs, investigating both, the turnaround success and the impact of turnaround on the family role in family firms. Based on a specifically developed integrated conceptual turnaround model, the author collected a sample of 209 turnaround cases of German medium-sized companies from restructuring experts working for German banks. Employing a variety of carefully selected statistical analyses he identifies key factors for turnaround success and finds specific archetypes of crises and turnaround. The study concludes with an analysis of the impact of a successful turnaround on the family firms within his sample. Based on the study's insights he provides both, recommendations for future research and a set of practical implications for all relevant stakeholders of a turnaround situation. Contents Conceptual Model of Crisis and Turnaround Analysis of the Turnaround Performance Archetypes of Crisis and Archetypes of Turnaround Impact of Turnaround on Family Ownership and Control Target Groups Researchers and students in the fields of strategic management, crisis & turnaround and family business Family firm managers and shareholders, credit risk managers working for German banks, management consultants with focus on crisis and turnaround The Author Dr. Thomas Wittig wrote his dissertation under the supervision of Prof. Dr. Andreas Hack at the Witten Institute for Family Business (WIFU) at Witten/Herdecke University.
Keywords: Small business -- Germany -- Finance.; Financial crises -- Germany -- History.; Germany.; elektronické knihy; electronic books